The role of vitamin D in the development and prevention of migraine: a review - Joanna Olszak; Karolina Zalewa; Wojciech Kapłan; Dominika Orłowska; Lidia Bartoszek (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Purpose  Migraine is a widespread neurological disorder characterized by severe, pulsating headaches often accompanied by nausea, vomiting, and hypersensitivity to light and sound. Although its exact cause is still under investigation, recent studies suggest that vitamin D deficiency may play a role in migraine occurrence and severity. Vitamin D, known primarily for its role in bone health, also affects the nervous and immune systems, and may influence inflammatory processes involved in migraine pathogenesis. This literature review aims to explore the relationship between vitamin D supplementation and the frequency and intensity of migraines, and whether supplementation could support migraine treatment.  Material and Methods  A comprehensive literature review was conducted using the PubMed database, focusing on articles published until the end of 2023. The search included the keywords: "vitamin D," "migraine," "headache," and "supplementation" in various combinations. Relevant studies were selected based on criteria such as monitoring vitamin D levels and the use of supplementation as an intervention in migraine patients.  Results  The results of the review suggest that vitamin D deficiency may be associated with an increased frequency of migraines. Supplementation with vitamin D was linked to a reduction in both the frequency and severity of migraines. While not all studies were consistent, the majority indicated that supplementation had a positive impact, particularly in individuals with vitamin D deficiency.  Conclusions  The findings suggest that vitamin D deficiency could be a risk factor for migraines, and that supplementation with vitamin D may help reduce the severity and frequency of migraine attacks. Although further research is required to establish optimal dosages and treatment protocols, vitamin D supplementation shows promise as a supportive therapy in migraine management.